Health Service Seeking Behavior in Suburban Communities - Pakaya, Nasrun; Hadjarati, Hartono; Abdulkadir, Widy Susanti; Duhe, Edy Dharma Putra; Handayani, Oktia Woro Kasmini; Budiono, Irwan (Jurnal Kesehatan Masyarakat, 2024)
Health problems in Indonesia today are the low health status of the community, among others, marked by high maternal mortality rates and infant mortality rates, on the other hand the use of health services is an important factor in determining health, which is influenced by geographical, economic and social aspects. The purpose of the study was to analyze the relationship between health service access factors and the determination of decisions on choosing family health services in suburban communities in Java and Outside Java. The method with a quantitative approach and support from qualitative data. The instrument consists of a questionnaire related to access to health services (geographic access, economic access, social access) related to the choice of health services. The population of families in the Sub-urban areas of Semarang and Gorontalo. Samples were taken using the accidental sampling technique, as many as 100 families. Data analysis with univariate, bivariate and multivariate analysis. The results of the study obtained significant differences in the decision to choose health services between the suburban communities of Semarang (Java) and Gorontalo (Outside Java), with a t-value of 4.284 and a sig value of 0.000. The difference lies in economic access. The choice of health services in suburban families in Java is more oriented towards choosing medical services such as hospitals and community health centers, while outside Java there are still quite a lot of families who choose traditional medicine as their health services.